2020
DOI: 10.1002/pbc.28166
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric oncology provider perspectives and practices: Supporting patients and families in schooling after cancer diagnosis

Abstract: Background Cognitive limitations are common after childhood cancer and require assessment and support in the medical and school setting. Pediatric oncology providers are tasked with educating families about the side effects of disease/treatment, and supporting families as they navigate the associated challenges. Despite this important role, little is known about the training, practice, and knowledge of providers in the domain of cognitive/school impacts. Methods An online survey was emailed to Children's Oncol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 40 publications
(71 reference statements)
0
25
0
Order By: Relevance
“…Furthermore, our review was limited to programmes that predominantly reported outcomes for the child with cancer and their parents. However, research suggests that siblings, peers, teachers, and healthcare professionals have distinct information and support needs in the process of delivering and advocating education support, which should be accounted for in future education support programmes 65‐67 . The scope of this review is limited by the exclusion of studies published in languages other than English.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Furthermore, our review was limited to programmes that predominantly reported outcomes for the child with cancer and their parents. However, research suggests that siblings, peers, teachers, and healthcare professionals have distinct information and support needs in the process of delivering and advocating education support, which should be accounted for in future education support programmes 65‐67 . The scope of this review is limited by the exclusion of studies published in languages other than English.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Communication between parents, educators, and medical teams is essential for optimal educational support for the PBT survivor, yet researchers consistently report communication problems and gaps among all stakeholders thus representing still another significant pain point for PBT survivors. For example, parents report feeling unprepared by the oncology team regarding their child’s educational needs [ 70 ], and at the same time, healthcare teams report being unsure about how to help parents navigate the complexities of school [ 57 ] and lack knowledge of specific criteria for eligibility for special services at school [ 71 ]. In addition, even if informed by the medical team of potential treatment-related limitations, individual healthcare providers may have different assessments and methods of communication of cognitive and academic risk, and parents may misunderstand those risks [ 72 ].…”
Section: Educational Pain Points For Pediatric Brain Tumor Survivorsmentioning
confidence: 99%
“…Two recent studies identified that around 50% of parents surveyed reported minimal to no education on the effect of cancer treatment on school performance while 77% of oncology providers reported a need for increased training on the cognitive effects and school reentry. 13,14 All of the cancer centers provided education to parents on school reentry, but the authors questioned whether the delivery or timing may have impacted the low parental recollection of this education. 14 The role of all of the rehabilitative therapists (PT, OT, and SLP) in providing education to families and providers on undergoing school transition should be considered in every multidisciplinary cancer team.…”
mentioning
confidence: 99%
“…13,14 All of the cancer centers provided education to parents on school reentry, but the authors questioned whether the delivery or timing may have impacted the low parental recollection of this education. 14 The role of all of the rehabilitative therapists (PT, OT, and SLP) in providing education to families and providers on undergoing school transition should be considered in every multidisciplinary cancer team. Improvement in this type of education allows parents to take on the new role of advocate and should be included within all disciplines that provide care to these children.…”
mentioning
confidence: 99%
See 1 more Smart Citation